Two new species of Xanthomicrogaster (Hymenoptera: Braconidae) from Argentina, with a key to species of the genus - Martínez, Juan José; Riverón, Alejandro Zaldívar (Zootaxa, 2018)
The genus Xanthomicrogaster is reported for the first time from Argentina. Two new species, X. sayjuhu Martínez sp. nov. from NE Argentina, and X. otamendi Martínez sp. nov. from the delta of the Parana River are described and illustrated. These include the first reports of the genus from temperate latitudes in South America. A key to species of Xanthomicrogaster is provided.